SHAPING THE BEHAVIOUR SOCIAL AWARE OF ENVIRONMENT - Saiful Hadi (Institut Agama Islam Negeri Madura)
AbstracKeeping, take care and rebuild environment and nature as equal as keep behaviour of individual life, group and society in order to make them have attitude to environment, manner to environmernt is a part of prosocial behaviour, because one of the meaning prosocial is individual freedom to tolerance, freedom to build and not destroy environment and surrounding, shaping attitude to environment is about international campigne about continously built that in man's soul there are integration between self harmony, harmony with of hers and harmony with nature. Those there aspects of harmony shoul be concreate through hard works and good tangibility activity through individual action in daily life. Activity of educational environment and issues campigne or environment program by social society organization and mass media.Kata-kata kunciprosocial behavior, society of environment aware